Reputation-based secyrity for heterogtneous structurally complex systems - Kussul, O.M. (Інститут програмних систем НАН України, 2015)
In this paper we present the service-oriented infrastructure within the Wide Area Grid (WAG) project that was carried out within the Working Group on Information Systems and Services of the Committee on Earth Observation Satellites (CEOS). The study focuses on enabling trust for this infrastructure using certificates and reputation-based model.